Green polymerizable deep eutectic solvent (PDES) type conductive paper for origami 3D circuits. Issue 18 (15th February 2018) - Ren'ai, Li; Zhang, Kaili; Chen, Guangxue; Su, Bin; Tian, Junfei; He, Minghui; Lu, Fachuang
Abstract : We report a green fabrication of conductive paper based on polymerizable deep eutectic solvents and its flexibility to origami electronics. Abstract : We report a green fabrication of conductive paper based on in situ polymerization of polymerizable deep eutectic solvents (PDESs) through a screen printing process. By pre-designed circuit paths and careful integration, on-demand input/output 3D circuits can be achieved, showing its flexibility to origami electronics.